Electromyographic analysis of riding posture during the bicycling start moment - Johnny Padulo; Luca Paolo Ardigò; Mirjana Milić; Douglas William Powell
Abstract Professional cyclists often adopt a competition-start standing posture, which has been shown to improve performance. The biomechanical basis of this is unclear, and might be due to a greater mechanical advantage or increased key muscle activity. Previous observations in steady state cycling showed greater activation of the tibialis anterior, erector spinae, and biceps brachii when adopting a standing vs. seated-riding posture. Little is known regarding the effect of riding posture on activation during a standing start. Eleven cyclists performed standing starts in seated and standing-postures using stationary-cycle and on the track. Electromyography of the gastrocnemius medialis, tibialis anterior, erector spinae, and biceps brachii was recorded during first and subsequent pedal strokes. Results showed that the gastrocnemius medialis did not modify activity. The tibialis anterior, erector spinae, and biceps brachii activity was increased during the standing posture compared to seated, only during the first pedal stroke. These increased activation intensities were accompanied by a corresponding 10% increase in bike speed during the first 5 meters following a standing start in the standing posture compared to the seated one. Adopting a standing posture during a standing start improves performance through greater initial acceleration.